Characterization of the probiotic properties of Lacticaseibacillus rhamnosus LR6 isolated from the vaginas of healthy Korean women against vaginal pathogens - Chung, Yusook; Kang, Seung Beom; Son, Dooheon; Lee, Ji Young; Chung, Myung Jun; Lim, Sanghyun (Frontiers in Microbiology, 2023)
The huma as an eco vaginal m fluctuatio diseases capacity t within thi study aim strain isol probiotic. publicly a carbohydr comprehe technique to assess and the va This is a provisional file, not the final typeset article pathogens, enhanced adherence to host cells, and high lactic acid production. Rat experiments revealed changes in both the fecal and vaginal microbiota; in treated rats, Firmicutes increased in both; Lactobacillaceae increased in the fecal samples; and Enterobacteriaceae decreased but Enterococcaceae, Streptococcaceae, and Morganellaceae increased in the vaginal samples. The study results provide evidence of the genetic characteristics and probiotic properties of LR6, and suggest that oral administration of L. rhamnosus LR6 can alter both gut and vaginal microbiome. Collectively, these findings establish L. rhamnosus LR6 as a highly promising candidate for improving vaginal health.